2016
DOI: 10.1111/age.12527
|View full text |Cite
|
Sign up to set email alerts
|

Three intronic lncRNAs with monoallelic expression derived from the MEG8 gene in cattle

Abstract: The field of long noncoding RNA (lncRNA) research has been rapidly advancing in recent years. Antisense lncRNAs, intergenetic lncRNAs and enhancer lncRNAs can regulate genomic imprinting, which leads to parent-origin-specific monoalletic expression of genes. However, the function of intronic ncRNAs in genomic imprinting remains unclear. Previously, we obtained the cDNA sequence of cattle MEG8 gene, which is located in the DLK1-DIO3 imprinted clusters of cattle chromosome 21. In this study, we undertook a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Although a vast majority of the unique reads were located in the exon region (on average: 78.50%), a considerable amount of them were still mapped to the intronic (10.45%) and intergenic (11.05%) regions ( Figure 2 a); in fact, it was revealed that in the intronic and intergenic regions, large amounts of noncoding RNAs could be transcribed from and perform essential molecular functions [ 42 , 43 ], so genome annotation work in cattle still needs to be constantly improved. Even if the breeds of Yunling and Leiqiong cattle are different, a majority of genes are expressed at quite similar levels between them ( Figure 3 a).…”
Section: Discussionmentioning
confidence: 99%
“…Although a vast majority of the unique reads were located in the exon region (on average: 78.50%), a considerable amount of them were still mapped to the intronic (10.45%) and intergenic (11.05%) regions ( Figure 2 a); in fact, it was revealed that in the intronic and intergenic regions, large amounts of noncoding RNAs could be transcribed from and perform essential molecular functions [ 42 , 43 ], so genome annotation work in cattle still needs to be constantly improved. Even if the breeds of Yunling and Leiqiong cattle are different, a majority of genes are expressed at quite similar levels between them ( Figure 3 a).…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq revealed that a considerable proportion of the uniquely mapped reads were located in the annotated intronic (on average:10.60%) and intergenic (16.40%) regions, indicating that the genome annotation of cattle is far from completed. In fact, as important regulators of molecular metabolism, many newly identified noncoding RNAs are transcribed from the intronic and the intergenic region[27,30,31].…”
mentioning
confidence: 99%
“…Long ncRNAs are endogenous RNA molecules with a length that ranges from 200 nt to 100 kb that lack open reading frames (ORFs). Based on their gene loci, characteristics, and relationship with their neighbor genes, the lncRNAs can be divided into 6 categories: (1) intergenic lncRNAs, also known as large intervening ncRNAs, or lincRNAs, which are defined as autonomously transcribed ncRNAs that do not overlap annotated coding genes, 11 such as lncRNA MALAT1, 12,13 LINK-A, 14 lncRNA ALIEN, 15 lncRAM, 16 and lncRNA UCC 17 ; (2) intronic lncRNAs, which are produced internally by an intron without any epitope of an ORF that overlaps at either end, such as lncRNA SPRY4-ITI 18 and lncRNA MEG8-IT1 19 ; (3) bidirectional lncRNAs, which start from the divergence direction of the promoter or enhancer region, typically within hundreds of base pairs; these lncRNA are also termed as enhancer-related RNA, [20][21][22] like lncRNA LEENE 23 and lncRNA HCCL5 24 ; (4) overlapping sense lncRNAs, which are transcribed in the same direction as an ORF and overlap with the ORF for at least one exon, such as lncRNA GAS5 25 ; (5) antisense lncRNAs, also known as natural antisense transcript, are transcribed from the antisense strand of an ORF, such as lncRNA GATA6-AS, 26 lncRNA ASBEL, 27 lncRNA UCHL1, 28 and lncRNA ANRIL 29 ; (6) lncRNAs that are hosted by an miRNA gene or an miRNA cluster, such as lncRNA LOC554202 30 and lncRNA MIR100HG. 31…”
Section: Definition and Classification Of Lncrnasmentioning
confidence: 99%